A New Class of Squaramide-Containing Phase-Transfer Catalysts: Application to Asymmetric Fluorination of β-Keto Esters - Wang, Bin; He, Yingdong; Fu, Xuancheng; Wei, Zhonglin; Lin, Yingjie; Duan, Haifeng (Synlett, 2015)
The squaramide moiety has proven to be a powerful hydrogen-bonding donor in organocatalysis, but chiral phase-transfer catalysts bearing the squaramide motif have not been reported so far. Reported herein is this kind of catalyst and their catalytic performance in the asymmetric fluorination of β-keto esters.
Keywords: organocatalysis; phase-transfer catalysis; asymmetric catalysis; fluorination; squaramides